Clinical Review: Navitoclax as a Pro-Apoptotic and Anti-Fibrotic Agent - Mohamad Anuar, Nur Najmi; Nor Hisam, Nur Syahidah; Liew, Sze Ling; Ugusman, Azizah (Frontiers in Pharmacology, 2020)
BCL-2 family proteins primarily work as a programmed cell death regulator, whereby multiple interactions between them determine cell survival. This explains the two major classes of BCL-2 proteins which are anti-apoptotic and pro-apoptotic proteins. The anti-apoptotic proteins are attractive targets for BCL-2 family inhibitors, which result in the augmentation of the intrinsic apoptotic pathway. BCL-2 family inhibitors have been studied extensively for novel targeted therapies in various cancer types, fibrotic diseases, aging-related as well as autoimmune diseases. Navitoclax is one of them and it has been discovered to have a high affinity towards BCL-2 anti-apoptotic proteins, including BCL-2, BCL-W and BCL-XL. Navitoclax has been demonstrated as a single agent or in combination with other drugs to successfully ameliorate tumor progression and fibrosis development. To date, navitoclax has entered phase I and phase II clinical studies. Navitoclax alone potently treats small cell lung cancer and acute lymphocytic leukemia, whilst in combination therapy for solid tumors, it enhances the therapeutic effect of other chemotherapeutic agents. A low platelet count has always associated with single navitoclax treatments, though this effect is tolerable. Moreover, the efficacy of navitoclax is determined by the expression of several BCL-2 family members. Here, we elucidate the complex mechanisms of navitoclax as a pro-apoptotic agent, and review the early and current clinical studies of navitoclax alone as well as with other drugs. Additionally, some suggestions on the development of navitoclax clinical studies are presented in the future prospects section.